2015
DOI: 10.1111/epi.13062
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital costs in patients with seizures and epilepsy after stroke

Abstract: SUMMARYObjectives: To verify the net effect of seizures after stroke on the use of in-hospital health care resources. Methods: Consecutive patients with first-ever stroke were admitted to the stroke unit of a Moscow hospital and followed prospectively until death or discharge. Each patient experiencing seizures was matched for age, sex, stroke type, National Institutes of Health Stroke Scale score at admission, and stroke risk factors to 2+ patients with no seizures, as controls. Resources consumed included le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Encephalopathy has a negative impact in overall neurological recovery of cancer patients [21, 31]. Moreover, patients with NCS and status epilepticus are also known to have poor neurological recovery [58]. Therefore, our cohort population of cancer patients with ongoing moderate to severe encephalopathy, and with a significant prevalence of NCS and NCSE, could reflect on our findings of poor neurological recovery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Encephalopathy has a negative impact in overall neurological recovery of cancer patients [21, 31]. Moreover, patients with NCS and status epilepticus are also known to have poor neurological recovery [58]. Therefore, our cohort population of cancer patients with ongoing moderate to severe encephalopathy, and with a significant prevalence of NCS and NCSE, could reflect on our findings of poor neurological recovery.…”
Section: Discussionmentioning
confidence: 93%
“…Electroencephalogram (EEG) monitoring is frequently used as part of the diagnostic work up of encephalopathic critically ill patients [5]. Patients diagnosed with seizures in the ICU usually have worse outcomes, including increased length of stay (LOS) and mortality, and increased ICU costs [58]. Moreover, they can have long-term medical consequences as more than 60% of patients diagnosed with NCS and NCSE have recurrent seizures after being discharged from the hospital [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our search yielded 71 studies (Figure 1). There was 1 ambispective, 20 prospective, 47 retrospective cohort studies, and 3 case-control studies. All studies were published in English, and we identified no studies in other languages.…”
Section: Resultsmentioning
confidence: 99%
“…2 Seizures after stroke could negatively affect the prognosis of the stroke and cause a decrease in quality of life. [3][4][5] The efficacy of intravenous (IV) recombinant tissue plasminogen activator (rt-PA) treatment for acute ischemic stroke has been demonstrated in many studies, and IV rt-PA treatment for acute ischemic stroke has been increasingly used around the world. 6,7 There is no consensus on how IV rt-PA treatment affects seizures after acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…2 Seizures after stroke could negatively affect the prognosis of the stroke and cause a decrease in quality of life. 3 4 5…”
Section: Introductionmentioning
confidence: 99%